Conscious Dying and the Metaphysics of Death: A Comparative and Interdisciplinary Analysis of Eastern and Western Perspectives - Parajuli, Deependra; Paudel, B. (Perspectives on Higher Education, 2025)
This study examines the phenomenon of conscious dying through the integrated lenses of Eastern philosophical traditions, contemplative science, and contemporary bioethical discourse. Rooted in teachings and final experiences of spiritual figures such as Gautama Buddha, Padmasambhava, Milarepa, Ramakrishna Paramhansa, and Swami Vivekananda, the article explores how meditative practices, ethical discipline, and detachment frame death not as an end, but as a consciously navigable transition. The concept of mahasamadhi—the volitional, lucid departure of realized beings—is examined alongside modern psychological and neuroscientific discussions on mindful dying, ego dissolution, and terminal lucidity. The paper also critically distinguishes between spiritual preparations for death and post-death cultural rituals, avoiding common conceptual conflations. Expanding beyond traditional analysis, the study engages with emerging technological interventions in assisted dying, such as the Sarco pod, to contrast mechanized autonomy with spiritual intentionality. Through a transdisciplinary framework, this article offers a nuanced dialogue between philosophy, neuroscience, ethics, and death studies, proposing that death may be understood not merely as biological cessation but as a threshold shaped by consciousness, culture, and care.